Successful laparoscopic cholecystectomy for gallbladder hemorrhage from a Dieulafoy lesion in a patient on hemodialysis: a case report - Yuu-ichi Yano; Tomohiro Iguchi; Shota Sato; Norifumi Iseda; Shun Sasaki; Yasuhiro Abe; Tomohiro Nakayama; Takuya Honboh; Seiya Kato; Noriaki Sadanaga; Hiroshi Matsuura (Surgical Case Reports, 2023)
Abstract Background Patients on long-term dialysis are prone to hemorrhagic complications, particularly uremic bleeding, but gallbladder hemorrhage is rare, even in patients on dialysis. There have been occasional reports of a Dieulafoy lesion being a cause of gastrointestinal hemorrhage, but its occurrence within the gallbladder is quite rare. This report describes a case of gallbladder hemorrhage from a Dieulafoy lesion in a patient on hemodialysis that was diagnosed early and successfully treated by laparoscopic cholecystectomy. Case presentation The patient was a 68-year-old woman on long-term hemodialysis with end-stage renal failure who presented with epigastralgia and back pain. There was no history of trauma or oral administration of antiplatelet or anticoagulant agents. There were no signs of an inflammatory reaction or hyperbilirubinemia. Contrast-enhanced computed tomography revealed a slightly hyperdense area in the distended gallbladder and extravasation within the gallbladder lumen but no gallstones. A severe atherosclerotic lesion was also found. She was diagnosed to have gallbladder hemorrhage and emergency laparoscopic cholecystectomy was performed. Although the postoperative course was complicated by drug fever, she was discharged on postoperative day 10 in a satisfactory condition. Histology revealed hemorrhagic ulceration with an exposed blood vessel accompanied by abnormal arteries in the submucosa. Arteriosclerosis with eccentric intimal hyperplasia in a small-sized artery was also seen. The diagnosis was gallbladder hemorrhage from a Dieulafoy lesion. Conclusions A Dieulafoy lesion should be kept in mind as a cause of gallbladder hemorrhage in a patient with severe arteriosclerosis and a bleeding diathesis, particularly if on dialysis, and treated as early as possible.